Methoxyl-substituted phosphine ligand properties and a case study of formation adducts to indium(III) bromide by DFT calculations. (1st October 2022) - Yang, Hui; Xing, Baoyan; Zhao, Jianguo; Ma, Guibin
Graphic abstract: Triphenylphosphine (PPh3 ) and its five bulky ligands substituted by different numbers of methoxyl groups at different phenyl ring position (such as TMP, TDP, o -Anis3 P, p -Anis3 P and m -Anis3 P) were studied by DFT calculations and by 31 P NMR spectroscopy. The different basicity and binding ability of these substituted ligands were shown to follow the trend TMP > TDP > o -Anis3 P > p -Anis3 P > m -Anis3 P > PPh3 . This trend is consistent with both In-P bond lengths and intramolecular interaction energies calculated for six adducts formed between these ligands and InBr3 . Highlights: We have conducted a systematic study of the donor properties of a series of bulky triarylphosphines with methoxyl substituents on the phenyl rings using Gaussian16 DFT calculations and 31 P NMR measurements in solution and in the solid state. The donation or bonding abilities of a series of methoxyl substituents is demonstrated with the trend TMP > TDP >  o -Anis3 P >  p -Anis3 P >  m -Anis3 P > PPh3 . Both substitution position and the number of methoxyl groups affected the ligand donation properties. A case study of six bulky phosphine ligands bonded adducts by DFT confirmed that this ligand bonding trend is accuracy by assessment In-P bond lengths of formed adducts. This bonding trend was proven by our analysis of three available crystal structures for indium(III) complexes, which confirmed the correlation between electron donation ability and chemical bonding distances. Abstract: Six bulky triphenylphosphine ligands containing substituted methoxyl groups (tris(2, 4, 6-trimethoxyphenyl)phosphine (TMP), tris(2, 6-dimethoxyphenyl)phosphine (TDP), tris( o -methoxyphenyl)phosphine ( o -Anis3 P), tris( p -methoxyphenyl)phosphine ( p -Anis3 P), tris( m -methoxyphenyl)phosphine ( m -Anis3 P) and triphenylphosphine (PPh3 )) were studied by DFT (density functional theory) calculations and experimental solution/solid-state 31 P NMR spectroscopy. The basicity and binding ability of these substituted ligands, proven by comparison of structural data with DFT-predicted data, are in the order TMP > TDP >  o -Anis3 P >  p -Anis3 P >  m -Anis3 P > PPh3 . Molecular structures for InBr3 with bulky ligands (TMP, TDP, o -Anis3 P, p -Anis3 P, m -Anis3 P and PPh3 ) were calculated using DFT. P-In bond distances generated from these six optimized molecular structures and the calculated intramolecular interaction energies are in agreement with the ligand properties, with strong donation ability for those with the short bond distance; the In-P bond distance from shortest to longest follows a similar trend as predicted by DFT calculations. DFT calculations for these adducts show that methoxyl substitution to triphenylphosphine (PPh3 ) ligands contributed to its electron donor ability resulting in lower P-In bond distances with relatively large bond interaction energies.